Dynamic metabolic response, clotting times and peripheral indices of central fatigue in horse competing in a 44 km endurance race - Arfuso, F.; Giannetto, C.; Interlandi, C.; Giudice, E.; Bruschetta, A.; Panzera, M. F.; Piccione, G. (Journal of Equine Veterinary Science, 2021)
A deep knowledge on metabolic response of athlete horse to exercise is of paramount importance for the development of optimal training programs to attain equilibrium between good performance and animal welfare. This study investigated the dynamic change of metabolic, clotting times and peripheral indices of central fatigue in horses competing in an official 44 km endurance race. From 6 horses blood samples were collected at rest (TPRE), within 5 minutes from the end of race (TPE5), after 30, 60 minutes after the end of race (TPE30 and TPE60) to investigate the values of blood lactate, glucose, platelets (PLTs), serum leucine, isoleucine, valine, tryptophan, the ratio between tryptophan and branched-chain amino acids (BCAAs) levels (Try/BCAAs), total proteins, non-esterified fatty acids, plasma thrombin time (TT), prothrombin time (PT), activated partial thromboplastin time and fibrinogen (Fb). Lactate, PLTs, non-esterified fatty acids, BCAAs and Try/BCAAs showed higher values at TPE5, TPE30and TPE60than TPRE(P < .0001); glucose showed lower values at TPE5, TPE30and TPE60than TPRE(P < .0001). Higher TT values were found at TPE5, TPE30and TPE60than TPRE, and at TPE5than TPE30 and TPE60(P < .0001); Fb was higher at TPE5than TPRE, T PE30and TPE60(P < .0001). This survey confirms that horses performing prolonged physical exercise experienced glycolysis, lipid mobilization and amino acid metabolism to provide substrates as fuel for muscle contraction.